Estimasi Koefisien Regresi Linear Berganda dengan Metode Goal Programming - Baiq Diah Fitasari (Jurnal Matematika, 2020)
The alternative method that can be used to determine the value of a multiple linear regression variable coefficient is goal programming method. The kind of data used in this research is secondary data namely the production of freshwater fish pond system data in the Province of West Nusa Tenggara based on Fisheries Service of West Nusa Tenggara Province year 2018. Software used to assist in reckoning is POM for Windows.Settlement calculation procedure in this research was conducted in two stages, namely the calculation with variable ????????4 and the calculation without variables ????????4. The results obtained with the variable ????????3 namely ????????1 = ????????0 = 64,08 ; ????????2 = ????????1 = 2,67 ; ????????3 = ????????2 = 0,27 ; ????????4 = ????????3 = 0, and the results obtained without variables ????????4 namely ????????1 = ????????0 = 64,08 ; ????????2 = ????????1 = 2,67 ; ????????3 = ????????2 = 0,24. The production of fresh water fish pond system in the Province of West Nusa Tenggara were affected by extensive fish ponds and food availability, while the number of domestic aquaculture freshwater fish do not affect production. Keywords : Multiple Linear Regression, Goal Programming, Production of Fish.